2006
DOI: 10.1002/eat.20271
|View full text |Cite
|
Sign up to set email alerts
|

Associations between juvenile delinquency and weight‐related variables: Analyses from a national sample of high school students

Abstract: Future research should examine risk and protective factors for unhealthy weight control behaviors and perceptions among delinquents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Youth involved with the criminal justice system are at even greater risk [4] with an estimated 88.7% of incarcerated youth reporting current use of alcohol [5]. Data support a relationship between alcohol use and risky sexual behavior among justice-involved youth [6].…”
Section: Alcohol Use Marijuana Use and Risky Sexual Behaviormentioning
confidence: 99%
“…Youth involved with the criminal justice system are at even greater risk [4] with an estimated 88.7% of incarcerated youth reporting current use of alcohol [5]. Data support a relationship between alcohol use and risky sexual behavior among justice-involved youth [6].…”
Section: Alcohol Use Marijuana Use and Risky Sexual Behaviormentioning
confidence: 99%
“…Research suggests that weight concerns are related to psychological and behavioral problems to a greater extent than actual BMI. 8,14,15 Among young men, weight concerns in general have been related to low self-esteem, 9 (but see Furnham and Calnan 3 ), depression, 8 decreased life satisfaction, 16 and use of alcohol and illicit drugs. 17 Weight concerns related to feeling underweight have been associated with experienced peer isolation, 7 low self-reported academic achievement, 4 exercise aimed at attaining a bigger body, 4,10 and increased intake of unhealthy, sugary foods.…”
mentioning
confidence: 99%
“…4 Weight concerns related to feeling overweight have been associated with somatic complaints 14 and delinquent behavior. 14,15 This study examines whether adolescent LBW boys report more weight concerns than boys the same age in the general population. It further examines the relationship of weight concerns to self-esteem and depression in the adolescent LBW boys, taking BMI into account.…”
mentioning
confidence: 99%
“…Most studies found a statistically significant association between factors studied and OW, and only in three studies (36)(37)(38) no association was found. Fourteen studies that assessed obesity as outcome, presented, in general, results similar to those observed for OW.…”
Section: General Characteristics Of Studiesmentioning
confidence: 90%
“…Seven studies (19,37,44,55,57,59,77) assessed psychological variables and, of these, three presented significant associations with OW. Directly associated with OW, both in boys and girls were: a higher score of depressive symptoms (77) ; presence of a food disorder characterizing a restrictive behavior (59) and the presence of trace of anxiety (19) .…”
Section: Psychological Variables and Owmentioning
confidence: 99%